Safety and Efficacy of an Absorbable Filter in the Inferior Vena Cava to Prevent Pulmonary Embolism in Swine - Huang, Steven Y. (Radiology, 2017)
PURPOSE: To evaluate the immediate and long-term safety as well as thrombus-capturing efficacy for 5 weeks after implantation of an absorbable inferior vena cava (IVC) filter in a swine model. MATERIALS AND METHODS: This study was approved by the institutional animal care and use committee. Eleven absorbable IVC filters made from polydioxanone suture were deployed via a catheter in the IVC of 11 swine. Filters remained in situ for 2 weeks (n = 2), 5 weeks (n = 2), 12 weeks (n = 2), 24 weeks (n = 2), and 32 weeks (n = 3). Autologous thrombus was administered from below the filter in seven swine from 0 to 35 days after filter placement. Fluoroscopy and computed tomography follow-up was performed after filter deployment from weeks 1–6 (weekly), weeks 7–20 (biweekly), and weeks 21–32 (monthly). The infrarenal IVC, lungs, heart, liver, kidneys, and spleen were harvested at necropsy. Continuous variables were evaluated with a Student t test. RESULTS: There was no evidence of IVC thrombosis, device migration, caval penetration, or pulmonary embolism. Gross pathologic analysis showed gradual device resorption until 32 weeks after deployment. Histologic assessment demonstrated neointimal hyperplasia around the IVC filter within 2 weeks after IVC filter deployment with residual microscopic fragments of polydioxanone suture within the caval wall at 32 weeks. Each iatrogenic-administered thrombus was successfully captured by the filter until resorbed (range, 1–4 weeks). CONCLUSION: An absorbable IVC filter can be safely deployed in swine and resorbs gradually over the 32-week testing period. The device is effective for the prevention of pulmonary embolism for at least 5 weeks after placement in swine. (©) RSNA, 2017